Exostoma tenuicaudata, a new species of glyptosternine catfish (Siluriformes: Sisoridae) from the upper Brahmaputra drainage, northeastern India - Tamang, Lakpa; Sinha, Bikramjit; Gurumayum, Shantabala Devi (Zootaxa, 2015)
Glyptosternines are highly specialized sisorid catfishes with greatly depressed body profiles; enlarged, horizontally extended paired fins, modified for adhesion, typically inhabiting torrential waters in rocky mountain streams and rivers. Their range of distribution extends from the upper reaches of the Amu Darya River drainage in Turkmenistan southwards and eastwards to Indochina and the Yangtze River (Changjiang) drainage of central China, and the Mekong and Salween drainages in northern and western Thailand (Vidthayanon et al. 2009; Ng & Vidthayanon 2014).